Does Compassion-Focused Therapy Training for Health Care Educators and Providers Increase Self-Compassion and Reduce Self-Persecution and Self-Criticism?. Issue 1 (2016) - Beaumont, Elaine; Irons, Chris; Rayner, Gillian; Dagnall, Neil
Abstract : Introduction: There is a growing body of evidence within the health care community suggesting that developing feelings of compassion can profoundly affect physical and psychological health. This is an important area of work, and initial research with nonprofessional groups has found that practicing compassion through a variety of experiential practices and meditations can lead to higher levels of compassion for others, sensitivity to suffering, motivation to help, and altruism. This study examines outcome measures after a 3-day introductory workshop on compassion-focused therapy provided to health care providers and educators. The aim of the research is to explore whether the training would increase self-compassion and reduce self-criticism and self-persecution. Methods: A total of 28 participants who were classified into three groups "nurses and midwives, " "counselors/psychotherapists, " and "other health care providers" completed the Self-Compassion Scale and Functions of Self-Criticizing and Self-Attacking Scale before and after training. Results: Results reveal an overall statistically significant increase in self-compassion and statistically significant reduction in self-critical judgment after training. There was no statistically significant reduction in self-persecution or self-correction scores after training. Discussion: Developing self-compassion and compassionately responding to our own "self-critic" may lead the way forward in the development of more compassionate care among health care professionals. Training people in compassion-based exercises may bring changes in levels of self-compassion and self-critical judgment. The findings are exciting in that they suggest the potential benefits of training health care providers and educators in compassion-focused practices.